2004
DOI: 10.1375/13690520460741426
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Individual Differences in Stressful Life Event Exposure in Male and Female Twins

Abstract: T he roles of genetic and environmental influences on stressful life events were examined in 3938 twin pairs (MZ, same-sex DZ, and opposite-sex DZ) using a sex-limitation model. Life events were assessed by personal interview, and were categorized as being either personal (i.e., events that occur directly to the individual) or network (i.e., events that occur to someone within the individual's social network, thus affecting the individual indirectly). Consistent with previous reports, genetic factors were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…First, we found that the association is greater between dependent (as compared to independent) negative life events and sleep quality. Second, we found substantial genetic influence on dependent negative life events, consistent with previous findings (35)(36)(37)(38)(39). Third, there was substantial overlap in the genes influencing poor sleep quality and those influencing dependent negative life events, suggesting gene-environment correlation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, we found that the association is greater between dependent (as compared to independent) negative life events and sleep quality. Second, we found substantial genetic influence on dependent negative life events, consistent with previous findings (35)(36)(37)(38)(39). Third, there was substantial overlap in the genes influencing poor sleep quality and those influencing dependent negative life events, suggesting gene-environment correlation.…”
Section: Discussionsupporting
confidence: 89%
“…Given the associations between sleep and negative life events it is possible that the genes influencing poor sleep quality also influence exposure to high risk environments. Indeed, certain environmental influences, such as dependent negative life events, show some degree of genetic influence (35)(36)(37)(38)(39), which suggests rGE. Analysing genetic liability to both sleep disturbance and the environmental stressors associated with sleep disturbance allows the detection of rGE.…”
Section: Gene-environment Correlation (Rge)mentioning
confidence: 99%
“…9,20,21 For example, studies of adult twins have shown that desirable and undesirable life events are moderately heritable 22,23 as are specific life events and life circumstances, including divorce, 24,25 the propensity to marry, 26 marital quality 27 and social support. [28][29][30] Studies in which researchers have measured child-specific aspects of the environment have also shown that putative environmental factors, such as parental discipline or warmth, are moderately heritable 12 (for reviews, see Plomin and Bergeman 20 ).…”
Section: Rge: Evidence From the Behavioral Genetic Literaturementioning
confidence: 99%
“…43,44 Similarly, personal life events (i.e., events that occur directly to an individual) are more highly heritable than network life events (i.e., events that occur to someone within an individual's social network, thus affecting the individual indirectly). 22 rGE: evidence from the molecular genetic literature…”
Section: Rge: Evidence From the Behavioral Genetic Literaturementioning
confidence: 99%
See 1 more Smart Citation